Organoleptic Test On Cheese From Goat's Milk With Coagulant Lemon Juice (Citrus Limon) - M. R. Hutasuhut; E. Mirwandhono; T.H. Wahyuni; Hasnudi; S Sepriadi (Jurnal Peternakan Integratif, 2020)
This study aims to determine the effect of lemon juice (Citrus Limon) on the coagulation process of milk. This research method used a 4 x 4 factorial completely randomized design with 2 replications of factor, which is factor A lemon juice levels, namely A0= 0.01% rennet, A1 = 5% lemon juice, A2 = 10% lemon juice, A3 = 15% lemon juice, and factor B is storage period, namely B0 = 0 days B1 = 5 days B2 = 10 days and B3 = 15 days. The variables measured were organoleptic tests including color, aromatic, and preferences (testy level). The results showed that from the addition of four levels of lemon juice used and four variations of Storage period, giving lemon juice level of 15% (A3) and storage period of 15 days (B3) is the optimal treatment to improve color, aromatic, and preferences in goat cheese and can be used as an alternative to replace rennet.